The Magnitude of Polypharmacy and Role of Disease Severity and Patient Sex in Medication Use Among Patients With MASLD Enrolled in TARGET ‐ NASH - Neuschwander‐Tetri, Brent A.; Morris, Heather L.; Mospan, Andrea R.; Yu, Feng; Munoz, Breda; Abraham, Sheenu; Fried, Michael W.; Barritt, A. Sidney; Al‐Sayyed, Leen; Sanyal, Arun J. (Alimentary pharmacology & therapeutics, 2025)
Polypharmacy is common among patients with multiple comorbidities but may compromise patient health due to medication interactions, cumulative side effects and compliance challenges. Characterise the extent of polypharmacy and assess the effects of sex, liver disease severity and comorbidities in patients with metabolic dysfunction associated steatotic liver disease (MASLD) in a real-world setting. Data from adults enrolled in TARGET-NASH, a real-world longitudinal observational cohort of patients with MASLD, were utilised. Reported medications were counted and relationships to disease severity, sex and insurance are described. Significant differences were identified using Chi-square or Fisher's exact test. Medication use was evaluated in 5190 adults (59% female) in the United States with the full spectrum of MASLD revealing that 90% were prescribed five or more medications and 75% were prescribed ten or more medications (63% of whom were females). Patients with cirrhosis were often prescribed nonsteroidal anti-inflammatory drugs (64%), opioids (55%), or benzodiazepines (45%). Females were prescribed more medications than males, particularly selective serotonin reuptake inhibitors (37% vs. 20%), opioids (44% vs. 37%), proton pump inhibitors (63% vs. 52%) and benzodiazepines (41% vs. 31%). Polypharmacy is common among patients with MASLD. Those with cirrhosis are most affected, and women with cirrhosis are at an even greater risk. Opioid, benzodiazepine, and nonsteroidal anti-inflammatory drug use is prevalent among patients with cirrhosis despite the known associated risks. Frequent medication use for chronic pain in patients with cirrhosis highlights the need for management plans that optimise safety balanced against therapeutic efficacy.